An Open-source Bayesian Atmospheric Radiative Transfer (BART) Code. I. Design, Tests, and Application to Exoplanet HD 189733b - Harrington, Joseph; Himes, Michael D.; Cubillos, Patricio E.; Blecic, Jasmina; Rojo, Patricio M.; Challener, Ryan C.; Lust, Nate B.; Bowman, M. Oliver; Blumenthal, Sarah D.; Dobbs-Dixon, Ian; Foster, Andrew S. D.; Foster, Austin J.; et al. (The planetary science journal, 2022)
We present the open-source Bayesian Atmospheric Radiative Transfer (BART) retrieval package, which produces estimates and uncertainties for an atmosphere’s thermal profile and chemical abundances from observations. Several BART components are also stand-alone packages, including the parallel Multi-Core Markov-chain Monte Carlo (MC3), which implements several Bayesian samplers; a line-by-line radiative-transfer model, transit ; a code that calculates Thermochemical Equilibrium Abundances (TEA), and a test suite for verifying radiative-transfer and retrieval codes, BARTT est . The codes are in Python and C. BART and TEA are under a Reproducible Research (RR) license, which requires reviewed-paper authors to publish a compendium of all inputs, codes, and outputs supporting the paper’s scientific claims. BART and TEA produce the compendium’s content. Otherwise, these codes are under permissive open-source terms, as are MC3 and BARTT est , for any purpose. This paper presents an overview of the code, BARTT est , and an application to eclipse data for exoplanet HD 189733b. Appendices address RR methodology for accelerating science, a reporting checklist for retrieval papers, the spectral resolution required for synthetic tests, and a derivation of the effective sample size required to estimate any Bayesian posterior distribution to a given precision, which determines how many iterations to run. Paper II, by Cubillos et al., presents the underlying radiative-transfer scheme and an application to transit data for exoplanet HAT-P-11b. Paper III, by Blecic et al., discusses the initialization and post-processing routines, with an application to eclipse data for exoplanet WASP-43b. We invite the community to use and improve BART and its components at http://GitHub.com/ExOSPORTS/BART/ .